(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article analyzes risk management and its impact on financial markets. Risk and capital management can happen anywhere in the stock market. This happens when an investor buys a desired stock in the stock market. Or it can happen when a financial fund manager with foreign currency derivatives avoids the risk of converting balance sheet assets and liabilities into foreign currency. Financial managers also use strategies such as asset allocation, portfolio diversification, and position pricing to reduce or effectively manage risk in the stock market. Although technical analysis of risk and capital management can provide useful information, it cannot completely eliminate an investor’s concerns. Risk management is a key part of capital markets, which involves recognizing, analyzing and mitigating the risks associated with trading activities[1]. Risk management aims to reduce losses and increase profits by predicting future risks and taking actions to prevent or mitigate them.